A Mixed‐Addenda Mo/W Organofunctionalised Hybrid Polyoxometalate. Issue 10 (10th March 2022) - Amin, Sharad S.; Cameron, Jamie M.; Winslow, Max; Davies, E. Stephen; Argent, Stephen P.; Robinson, David; Newton, Graham N.
Abstract: A mixed‐addenda W/Mo hybrid polyoxometalate cluster – K6 [P2 W15 Mo2 O61 (POC6 H5 )2 ] (1 ) was synthesised from the condensation of K10 [P2 W15 Mo2 O61 ] and PO3 C6 H7 under acidic conditions. Single‐crystal X‐ray diffraction confirmed the structure of the hybrid cluster and the presence of two Mo centres in the cap of the lacunary cluster. The electronic effects of metal substitution were studied by cyclic voltammetry, spectroelectrochemistry and electron paramagnetic resonance spectroscopy and supported by density functional theory calculations. Comparing 1 to its tungsten‐only analogue K6 [P2 W17 O61 (POC6 H5 )2 ] (2 ), a more positive potential for the first reduction process was induced by the substitution of W for Mo, consistent with a significant lowering of the cluster LUMO energy. Abstract : Substitution of metal addenda was explored as a method to modulate the electronic structure of organofunctionalised hybrid polyoxometalate clusters. Here we study the effects of Mo substitution into a W‐based cluster. Through a range of spectroscopic and electrochemical techniques, substitution of W for Mo was shown to significantly modify the frontier orbital energies of the hybrid cluster.